2014
DOI: 10.1186/s40001-014-0065-5
|View full text |Cite
|
Sign up to set email alerts
|

Diverse expression of selected cytokines and proteinases in synovial fluid obtained from osteoarthritic and healthy human knee joints

Abstract: BackgroundOsteoarthritis (OA) is defined by signs and symptoms of inflammation within the affected joint. The aim of this study is to determine the mRNA expression levels of selected cytokines and matrix-metalloproteinases of cells found in synovial fluid (SF) obtained from osteoarthritic knee joints compared to healthy controls.MethodsSF was obtained from 40 patients undergoing total knee arthroplasty due to evident OA and from 10 healthy controls. Expression of TNF-α, IL-1β, MMP-1 and MMP-3 was assayed among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The expression of MMP1 and MMP3 has also been shown to be elevated in the synovial fluid of patients with OA 24 . A recent animal study demonstrated elevated expression of MMP1 and MMP3 from the menisci of knees with OA compared to menisci from knee without OA 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MMP1 and MMP3 has also been shown to be elevated in the synovial fluid of patients with OA 24 . A recent animal study demonstrated elevated expression of MMP1 and MMP3 from the menisci of knees with OA compared to menisci from knee without OA 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation associated with our study is that it did not include an evaluation of matched, non‐injured control subjects with normal joints, or measurement of aggrecanases (ADAMTS‐4 and ‐5). We did not expect subjects with normal knees to have variable levels of the analytes that were considered in the current study as prior work has demonstrated that they either do not vary over time or are very low and cannot be detected in subjects with normal knees and no history of prior injury or disease . This study drew from two separate cohorts that have similar characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for determination of drug concentration were collected at Time 0 (prior to drug administration) and at 15, 30 and 45 min, and 1, 2, 3,4,5,6,8,12,18,24,36,48,72 and 96 h post administration. Subsequent samples were collected every other day until 49 days post administration.…”
Section: Collection Of Synovial Fluid and Plasmamentioning
confidence: 99%